Geomorphology and sedimentary processes on the Sloggett Canyon, Northwestern Scotia Sea, Argentina - Palma, Fermin Ignacio; Bozzano, Graziella; Principi, Sebastián; Isola, José Ignacio; Ormazabal, Juan Pablo; Esteban, Federico Damián; Tassone, Alejandro Alberto (Journal of South American Earth Sciences)
The southern Argentine Continental Margin hosts the Tierra del Fuego Submarine Canyon System, located in the northwestern Scotia Sea, and formed by 4 main canyons: Valentín, Sloggett, Nueva Canyon, and Wollaston. This region is especially interesting due to its complex tectonic setting and its proximity to the polar regions where intense bottom currents associated with the Argentine Contourite Depositional System take place. Here, we present for the first time the complete high-resolution swath bathymetry, 28 m grid size, of the Sloggett Canyon obtained during the YTEC-GTGM 0 cruise on board the Argentine R/V Austral. This new information allowed us to make a detailed morphosedimentary description of the architectural elements of the canyon and to identify the main sedimentary processes that controlled its formation and evolution together with other oceanographic, climatic, and tectonic ruling factors. The Sloggett Canyon, with a total length of 147 km, starts in the continental shelf with the head area located at 90 m water depth, only 8.5 km away from the coast, and ends at 3690 m water depth joining the abyssal Yahgán Basin. It is deeply carved into the continental slope, with 1600 m as the maximum incision observed in its middle sector. The canyon head area is characterized by two different tributary systems that act as routing conduits for sediment supply from the shelf to the canyon domain. On the western flank, the tributary system is densely spaced with deeply incised V-shaped valleys that suggest the occurrence of active sediment flows that probably evolve into erosive turbidity currents. On the eastern flank, on the contrary, the tributary channels are sparse less incised, and U-shaped, suggesting that they are no longer active. Here, mass wasting processes seem to dominate as evidenced by the presence of slumping and sliding scars. The canyon valley shows two predominant orientations, NW-SE and NE-SW, with sharp bends of approximately 90°. These orientations would have been controlled by the ...